Session Topic: Recognizing the Impact of Growth: Discussion - Malkiel, Burton G.; Arditti, Fred D.; Gupta, Manak C. (Journal of Finance, 1975)
Burton G. Malkiel, Fred D. Arditti, Manak C. Gupta, Session Topic: Recognizing the Impact of Growth: Discussion, The Journal of Finance, Vol. 30, No. 2, Papers and Proceedings of the Thirty-Third Annual Meeting of the American Finance Association, San Francisco, California, December 28-30, 1974 (May, 1975), pp. 548-555